THE IMPACT OF POOR SANITATION ON TOURISM DEVELOPMENT: A GLOBAL REVIEW - Vita Elysia; Ake Wihadanto (Universitas Trisakti, 2020)
Aim: The objective of this paper is to review the impact of poor sanitation on global tourism development. Methodology and Results: The majority of the data for this study was sourced from World Development Indicators (WDI) dataset for more than 200 countries in 2014 from the World Bank. A regression analysis was applied to analyze the impact of access to improved sanitation on tourism development by using some indicators such as the number of tourist arrivals, the proportion of the population using improved sanitation facilities, and the proportion of the population using improved water facilities. The study found that the relationship between the proportion of the population using improved sanitation facilities and the number of tourist arrivals is significant. Poor sanitation has been shown to have huge negative impacts on public health and the economy. In terms of the economic impacts, the lack of access to improved sanitation causes economic losses related to the direct costs of treating sanitation-related diseases and the indirect cost of lost income through reduced productivity. Conclusion, significance, and impact study: Access to basic sanitation facilities is regarded as one of the aspects that should be considered to support the tourism industry, particularly in developing countries. This study suggests that providing sanitation is the best investment for promoting tourism. Decision-makers should act now, and in a concerted way, to provide adequate sanitation services and at the same time sustaining tourism growth as an essential aspect of a country’s economy.